Design and Formulation of Once Daily Naproxen SustainedRelease Tablet Matrix from Methocel K 15M CR and Methocel K 100M CR: Formulation of naproxen SR tablet matrix - Harun-Or-Rashid; Md. Zakir Hossain; Abu Shara Shamsur Rouf; Abul Kalam Lutful Kabir (Iranian Journal of Pharmaceutical Sciences, 2009)
The purpose of this work was to develop once daily sustained release (SR) matrix tablets of naproxen, an anti-inflammatory agent. The tablets were prepared by wet granulation method along with hydrophilic matrix materials like Methocel K 15M CR and Methocel K 100M CR. The granules were evaluated for bulk density, angle of repose, compressibility index, total porosity and drug content. The tablets subjected to thickness, diameter, weight variation test, drug content, hardness,friability, and in vitrorelease studies in buffer medium (pH, 7.4). The granules prepared either by Methocel K 15M CR or Methocel K 100M CR did not show satisfactory flow properties and compressibility, and had difficulty in sieving and individual in drug release. On the other hand, tablet matrix prepared along with Methocel K 15M CR and Mehtocel K 100 LVCR polymers of the proposed formulation F-8 showed desired drug release up to 24 h. All the formulations followed first order release kinetics (except F-2 and F-4), exhibited diffusion dominated drug release when data plotted into Korsmeyer Peppas equation. The matrix tablet of naproxen using hydroxypropyl methylcellulose derivatives controls the drug release effectively for 24 h; hence, the formulation can be considered as once daily sustained release tablet of naproxen in order to improve patient compliance.